Indigenous Mother and Children at Las Islas Clinic - Bacon, David
OXNARD, CA - At the Las Islas Clinic in Oxnard pregnant women and mothers and children from Oaxaca and Guerrero receive health care in their native Mixtec language. Pictured: Irma Tiburcio, daughters Maria and Yesenia, and baby Naftali